Strategi Pengelolaan Kapasitas Bandwidth Untuk Mendukung Layanan Komunikasi Informatika Yang Dibutuhkan Di Kantor Gubernur Sumatera Utara - Mhd. Murini Ramadhani; Andhika Fisryansah Ahlief Putra; Muhammad Ikhsan; Muhammad Iqbal Nahwi (Journal Of Informatics And Busisnes, 2024)
Bandwidth capacity management is one of the important aspects in computer network management, especially in the context of local government agencies that rely on online services. Adequate bandwidth capacity is required to provide unhindered public services, provide quick access to information that supports decision-making, and adapt to dynamic growth. This study aims to optimize network access capacity at the North Sumatra Governor's Office by identifying ways to improve the efficiency of bandwidth capacity usage in supporting government communication services. This research uses a mikrotik approach to regulate data traffic paths and optimize the use of network resources. The results showed that proper bandwidth management can increase network access speed and reduce data traffic congestion. This has a positive impact on the quality of government communication services, such as the ease and speed of information exchange between agencies in North Sumatra and between the North Sumatra Governor's Office and the Central Government.